2015
DOI: 10.1002/2015gl066389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Operation IceBridge quick‐look snow depth estimates on sea ice

Abstract: We evaluate Operation IceBridge (OIB) “quick‐look” snow depth on sea ice retrievals using in situ measurements taken over immobile first‐year ice (FYI) and multiyear ice (MYI) during March of 2014. Good agreement was found over undeformed FYI (−4.5 cm mean bias) with reduced agreement over deformed FYI (−6.6 cm mean bias). Over MYI, the mean bias was −5.7 cm, but 54% of retrievals were discarded by the OIB retrieval process as compared to only 10% over FYI. Footprint scale analysis revealed a root‐mean‐square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
7
35
0
Order By: Relevance
“…If samples with rough-ness > 10 cm were not included in the comparisons, there would be a consistent decrease in the standard deviation of the differences for all retrievals. This suggests that all the retrievals seem to be affected by surface roughness, consistent with the results reported by King et al (2015). However, the correlation values did not increase for all algorithms (NSIDC: 0.29 to 0.34; GSFC-NK: 0.45 to 0.61; SRLD: 0.66 to 0.71; Wavelet: 0.72 to 0.67; JPL: 0.63 to 0.60).…”
Section: Comparisons With Snow Depth From Eurekasupporting
confidence: 80%
See 2 more Smart Citations
“…If samples with rough-ness > 10 cm were not included in the comparisons, there would be a consistent decrease in the standard deviation of the differences for all retrievals. This suggests that all the retrievals seem to be affected by surface roughness, consistent with the results reported by King et al (2015). However, the correlation values did not increase for all algorithms (NSIDC: 0.29 to 0.34; GSFC-NK: 0.45 to 0.61; SRLD: 0.66 to 0.71; Wavelet: 0.72 to 0.67; JPL: 0.63 to 0.60).…”
Section: Comparisons With Snow Depth From Eurekasupporting
confidence: 80%
“…Increased snow depth was associated with local regions of deformed ice where drifted accumulation was found in proximity to convergence features (i.e., rafting, rubble, and pressure ridging). Those areas were described as deformed FYI in King et al (2015) and were shown to have a higher mean depth of 20.7 ± 11.4 cm. Transect variations in density were conservative, with a mean of 306 kg m −3 and standard deviation of 50 kg m −3 , which is comparable to the assumed climatological mean of ∼ 320 kg m −3 near the end of the winter.…”
Section: Eureka 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…Areas of thick ice, such as ridges in an otherwise smooth FYI zone can be underestimated if they are proximal to areas of thin ice and occur with the footprint of the EM sensor. Unfortunately, it was not possible to obtain co-located in situ snow depth observations in our study area and due to the uncertainties associated with snow depth estimates in complex ice environments Operation IceBridge (OiB) and CryoVex data were not included in the analyses [40]. We were able to obtain in situ snow depth measurements, which were collected using a MagnaProbe near Eureka in the CAA between 8 and 15 April 2016 (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, MYI f p is not significantly correlated with surface roughness. Surface roughness can be defined for scales ranging from meters to kilometers, with footprint-scale uncertainties such as snow roughness and errors associated with sensor position during airborne measurement acquisition (yaw and pitch angles, and slant range distortion) exhibiting a stronger effect on the measurements than at larger spatial scales [26,40]. In order to minimize the influence of measurement uncertainty on surface roughness measurements we performed a moving average on the surface roughness data (~2400 m) and found stronger correlations between surface roughness and f p for both FYI (r s = −0.84) and MYI (r s = −0.34).…”
Section: Discussionmentioning
confidence: 99%